Contrasting changes in abundance of Falcated Duck Mareca falcata wintering in the Yangtze River floodplain and on the eastern coast of China - Zhang, Beixi; Wang, Xin; Meng, Fanjuan; Kharitonov, Sergey; Hu, Binhua; Gao, Dali; Liu, Guanhua; Zhang, Yong; Antonov, Aleksei; Batmunkh, Davaasuren; et al. (Wildfowl, 2020)
The Falcated Duck Mareca falcata, which is considered Near Threatened by IUCN, winters almost exclusively in East Asia, with greatest numbers occurring in the Yangtze River floodplain and along the coasts of eastern China. Given gaps in knowledge of its distribution and population status, we combined tracking studies, winter surveys and expert knowledge, to revise the geographical definition of its summer range in eastern Russia, Mongolia and Japan, and the main wintering range in China, South Korea, Japan and India. Data from six tagged individuals tracked on migration between their wintering and breeding grounds, combined with a single ring recovery, indicated that Falcated Ducks wintering in the Yangtze River migrate via the Northeast China Plain to breed over an extensive area in eastern Russia and northeast China. However, in the absence of telemetry data from birds wintering in the Indian sub-continent, Japan and the Korean Peninsula, we cannot yet define a flyway structure for the species. Mid-winter field surveys of Yangtze River floodplain wetlands in January 2004/05, 2015/16 and 2019/20 showed Falcated Ducks to be widely distributed, with 17 key sites supporting > 93% of the total wintering numbers counted in the region. Falcated Ducks in the Yangtze River floodplain increased from c. 15,000 counted in winter 2004/05, to c. 40,000 in 2015/16, and 88,000 in 2019/20, ascribed to a combination of improved survey coverage as well as increases in local abundance (based on sequential counts at key sites in 2004/05, 2015/16 and 2019/20). Coastal surveys undertaken in eastern China in winters 2003/04–2006/07 identified two key sites, which together supported 84.9% of the 14,904 individuals recorded. Between 2015/16 and 2019/20, abundance at these two sites had declined by 78.8% and 99.4% respectively, likely attributable to habitat loss through land reclamation during that period. More telemetry research, combined with comprehensive surveys of wintering, stopover and breeding sites is required to improve our understanding of migratory connectivity and the major migration routes of this species. The wide distribution of Falcated Duck also requires further comprehensive surveys in other wintering areas (e.g. central China and along the eastern coasts of China) to track changes in local abundance within its winter quarters, which in turn should confirm whether increases in abundance in the Yangtze River floodplain reflect an increase or a redistribution of the population. Long-term monitoring and sympathetic management of key staging and wintering sites used by the Falcated Duck in China, and across the rest of its range, are also required to ensure the efficacy of conservation measures for the long-term survival of the species.